USE OF QUALITY INDEX FOR EVALUATION OF WATER IN LENTIC ENVIRONMENT - Goveia, D.; Rebelo, A.; Loro, A. P.; Sasso, G. D.; Da Rocha, T. N. F.; Dompieri, T. P.; Carlos, V. M. (Revista Brasileira de Engenharia de Biossistemas, 2014)
Aquatic systems that have calm waters and bounded region, eg, ponds, lakes and swamps, are called lentic environments. The Park Carlos Alberto de Souza located in Sorocaba city, Sao Paulo State, is one of the parks in the city containing artificial lake area is home fish, turtles and herons. It is frequented by children and adults for leisure or exercise. Thus, good quality water is essential for life on the lake. The objective of this study was to analyze the water quality using quality indexes adopted by CETESB (Companhia de Tecnologia de Saneamento Ambiental). The results showed a high amount of fecal coliform and low oxygen concentration. Considering the weight of each parameter the water was classified as good. The index related to the presence of nutrients classified as hypertrophic water body, which can cause proliferation of algae and fish mortalities. The results represent a warning about the need to monitor the quality of lentic and need alert the population who frequent the place.